The Transformative Evolution of Conference Management Systems (Journal of Digital System Development, 2024)
Once reliant on manual processes and paper-based submissions, academic conferences have evolved into dynamic platforms for knowledge sharing, collaboration, and innovation through Conference Management Systems (CMS). CMS has become a key driver of change and progress in conference organisations. These centralised hubs connect authors, reviewers, organisers, and attendees. To date, various CMS models have been developed with different features. Understanding these features is crucial to ensure that conference organisers receive the best support. A previous study has reviewed various CMS platforms, highlighting their distinct features and strengths. However, this research needed to address CMS technology's evolution and future advancements. Through a literature review and comparative analysis of CMS features, this paper outlines the typical features of CMS that can be useful for organisers. Further, this paper explores the transformative evolution of CMS and looks ahead to the promising future. This evolution reflects a dedication to continuous innovation, adapting to changing needs, and embracing advanced technologies to enhance user experiences while ensuring security and privacy. The future of CMS is marked by innovation, adaptability, and a solid commitment to providing improved experiences for all conference stakeholders.